Fuentes Romero, Juan. Las bibliotecas públicas: crisis, oportunidades y desafíos. Buenos Aires: Alfagrama, 2013, 268 págs. ISBN: 978-98-713-05735. - Gómez Hernández, José Antonio (Anales de Documentación, 2014)
Reseña